The Influence of Managerial Ownership, Profitability on Company Value with Dividend Policy As Moderation - Almayda Flabiya; Sunarto Sunarto (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2022)
Abstract: This study aims to analyze and examine the effect of managerial ownership, profitability on firm value with dividend policy as moderating. The population used in this study is all mining companies that have been listed on the Indonesia Stock Exchange (IDX) in 2017-2019. The sampling method used in this research is using porpusive sampling technique. The results of this study explain that managerial ownership has a positive effect on firm value, while profitability cannot affect firm value. Dividend policy has a negative effect on firm value. Dividend policy cannot moderate the effect of managerial ownership on firm value, while dividend policy can moderate profitability on firm value. Keywords: Dividend Policy, Firm Value, Managerial Ownership, Profitability